EB1 Is Essential for Spindle Formation and Chromosome Alignment During Oocyte Meiotic Maturation in Mice. (April 2021) - Zhou, Dongjie; Nie, Zheng-Wen; Cui, Xiang-Shun
Abstract : The cytoskeleton plays an orchestrating role in polarized cell growth. Microtubules (MTs) not only play critical roles in chromosome alignment and segregation but also control cell shape, division, and motility. A member of the plus-end tracking proteins, end-binding protein 1 (EB1), regulates MT dynamics and plays vital roles in maintaining spindle symmetry and chromosome alignment during mitosis. However, the role of EB1 in mouse oocyte meiosis remains unknown. Here, we examined the localization patterns and expression levels of EB1 at different stages. EB1 protein level was found to be stable during meiosis. EB1 mainly localized along the spindle and had a similar localization pattern as that of α -tubulin. The EB1 protein was degraded with a Trim-Away method, and the results were further confirmed with western blotting and immunofluorescence. At 12 h of culture after EB1 knockdown (KD), a reduced number of mature MII oocytes were observed. EB1 KD led to spindle disorganization, chromosome misalignment, and missegregation; β -catenin protein binds to actin via the adherens junctional complex, which was significantly reduced in the EB1 KD oocytes. Collectively, we propose that the impairment of EB1 function manipulates spindle formation, thereby promoting chromosomal loss, which is expected to fuel aneuploidy and possibly fertilization failure.